Risk factors for the development of neurotoxic syndromes from the use of CAR-T cells: An integrative review (Research, Society and Development, 2025)
CAR-T immunotherapy is an innovative and technologically complex treatment that has proven effective in hematopoietic cancers. However, adverse effects such as neurotoxic syndromes may occur. The objective of this study was to analyze the risk factors associated with the development of neurotoxic syndromes after CAR-T immunotherapy infusion. This is an integrative review with a qualitative and exploratory approach. The research was conducted in the PubMed database, between 2020 and 2025, using the search strategy: “CAR-T Cell* Therapy” OR “Immunotherapy AND CAR-T Cell*” AND “Neurotoxicity Syndrome*” OR “Cell-Associated Neurotoxicity”; PRISMA2020 criteria were used, and after applying inclusion and exclusion criteria, the selected studies were qualitatively analyzed according to the steps of Discursive Textual Analysis. After applying the inclusion and exclusion criteria, 13 articles were selected to compose the study. The factors associated with higher risks of CRS and ICANS due to CAR-T immunotherapy identified are: types of CAR products, inflammatory interleukins released simultaneously, high tumor burden, acute kidney injury, sepsis, history of neurological injury, abrupt onset of neurotoxic symptoms, and high lactate dehydrogenase rates. It is inferred that several factors influence the risks of neurotoxicities, contributing to the complexity of this effect, making it necessary to conduct additional studies to deepen the understanding of the mechanisms involved, identify other possible risk factors, and enable the standardization of pharmacological management protocols for affected patients.